Analisis Kebutuhan Pengembangan Media Bedug Elektronik Berbasis Etno-STEM di Sekolah Dasar - Elsakira, Lena; Putri, Agnestasia Ramadhani; Mulyati, Srie (Edukasi: Jurnal Penelitian dan Artikel Pendidikan, 2026)
Natural Science education in elementary schools continues to face significant challenges, particularly regarding the scarcity of concrete and contextual learning media capable of fostering students' critical thinking skills, especially on the topic of energy sources and their transformations. The Bedug, a traditional drum deeply rooted in students' local culture, presents a strategic opportunity to be utilized as a learning medium by integrating STEM (Science, Technology, Engineering, and Mathematics) principles to facilitate critical thinking. This research aims to analyze the necessity of developing an Ethno-STEM-based electronic Bedug for elementary school settings. A qualitative descriptive approach was employed, with data gathered through structured and unstructured interviews with fourth-grade teachers and students. The findings reveal that teachers struggle to explain energy transformation concepts concretely, as existing media are limited to audiovisual formats that fail to represent various energy changes optimally. Furthermore, project-based and engineering activities remain infrequent, hindering the development of students' critical thinking. Conversely, students demonstrated high interest in science learning linked to local culture, specifically the Bedug and the Ngadulag tradition. They also expressed curiosity about the electronic Bedug concept and were able to articulate basic relationships between sound and electrical energy. These findings indicate that an Ethno-STEM-based electronic Bedug is urgently needed as a concrete, interactive, and contextual learning tool. This media effectively merges cultural heritage with modern technology, providing a superior solution compared to conventional media in supporting conceptual understanding and critical thinking skills.